PELESTARIAN LINGKUNGAN HIDUP MELALUI HUKUM ADAT TRADISI NYADRAN (STUDI EMPIRIS DI WILAYAH DESA BRONGKOL KECAMATAN JAMBU KABUPATEN SEMARANG) - Susila, Esdarwati; Rizky Irfan, Hutomo; Lailasari, Ekaningsih; Ridho Sa'dillah, Ahmad; Nur, Hidayah (Fakultas Hukum Universitas Muhammadiyah Cirebon, 2024)
Environmental preservation through the Nyadran traditional law is an approach that integrates cultural values ​​and local wisdom in an effort to protect the ecosystem. The nyadran tradition commonly practiced by Javanese people not only functions as a spiritual ritual but also reflects the harmonious relationship between humans and nature. In practice, nyadran involves cleaning the environment, caring for nature, and strengthening communities in protecting natural resources. This writing aims to examine the role of customary law in supporting environmental preservation through the nyadran tradition and its impact on public awareness of the importance of the environment. Keywords: Environmental preservation; the Nyadran;, Traditional Law.